Heme proteins--diversity in structural characteristics, function, and folding. - Smith, L; Kahraman, A; Thornton, J (2010)
The characteristics of heme prosthetic groups and their binding sites have been analyzed in detail in a data set of nonhomologous heme proteins. Variations in the shape, volume, and chemical composition of the binding site, in the mode of heme binding and in the number and nature of heme-protein interactions are found to result in significantly different heme environments in proteins with different functions in biology. Differences are also seen in the properties of the apo states of the proteins. The apo states of proteins that bind heme permanently in their functional form show some disorder, ranging from local unfolding in the heme binding pocket to complete unfolding to give a random coil. In contrast, proteins that bind heme transiently are fully folded in their apo and holo states, presumably allowing both apo and holo forms to remain biologically active resisting aggregation or proteolysis. The principles identified here provide a framework for the design of de novo proteins that will exhibit tight heme ligand binding and for the identification of the function of structural genomic target proteins with heme ligands.